KOMPARASI HASIL BELAJAR KOGNITIF SISWA ANTARA PENGGUNAAN LKS BERBASIS LEARNING CYCLE 3 FASE DAN NON LKS PADA MATERI REAKSI REDOKS KELAS X SMA NEGERI 10 BANJARMASIN - Amrullah Yasir Maulidi; Abdul Hamid; Leny Leny (Universitas Lambung Mangkurat, 2014)
Abstract. Research has been done about usage of student worksheets based 3-phase learning cycle. This research aims to (1) determine differences in cognitive achievement between students who use student worksheets based 3-phase learning cycle with students who use 3-phase learning cycle model without student worksheets of redoks reactions (2) determine student response to usage of student worksheets based 3-phase learning cycle. This research method is a quasi-experiment. Samples were students of class X-1 and X-2 SMA Negeri 10 Banjarmasin amount to 66 people. The research design was used the nonequivalent control group design. Collecting data using achievement test and question form responses. Data were analyzed using t-test with a significance level of 5%. Percentages techniques used for the analysis of the response. Calculation of the t-test showed that ttest > ttable so that concluded that there is a significant difference in learning result between the experimental class and control class. As for the response of the students as much as 88.43% gave a positive response in the experimental class and 86.18% of students gave a positive response in the control class.Keywords: worksheets based 3-phase learning cycle, learning result, student response, redoks reactions